Using WordPress - Hussey, Tris.; Safari eBooks (Indianapolis, Ind. : Que, 2011)
"Using Wordpress" is a customized, media-rich learning experience designed to help new users master Wordpress quickly, and get the most out of it, fast. The book and online content work together to teach everything mainstream Wordpess users need to know.
Domains and hosts: getting the foundation in place -- Installing WordPress on your own server -- Getting around WordPress -- Configuring WordPress to work its best -- How WordPress.com is different than WordPress.org -- Finding and using plugins -- All about themes -- Organizing the content on your blog -- Creating and managing content with WordPress -- Creating sites with WordPress -- Tuning WordPress for search engines -- Managing multimedia with WordPress -- Maintaining WordPress -- Understanding WordPress security -- Troubleshooting common problems.
Description based on print version record.
Includes index.
Keywords: WordPress (Electronic resource); Blogs -- Computer programs; Web sites -- Authoring programs; Electronic books